2011
DOI: 10.1108/09684881111158072
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' attitudes towards training in ICT: a critical approach

Abstract: PurposeThe aim of the present study is to investigate why teachers participate in Information and Communication Technology (ICT) programmes, what their sociological approaches are, and where they focus their attention in order to achieve the objectives of their training in these new technologies.Design/methodology/approachThe sample group of this research consists of 162 teachers who work in primary schools in Northern Greece. There were 70 (43.2 percent) men and 92 (56.8 percent) women. For the fulfilment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
1
7
0
1
Order By: Relevance
“…Funding in education, but also in the introduction of ICT, plays a dominant role in upgrading the quality of education, but also in changing pedagogical-teaching practices, according to their views. Similar findings have been found in other research, highlighting the need to support teachers through training and changing culture and practices in education (Giavrimis & Giossi, 2011), but also to increase the financial resources available to upgrade the teacher's project (Spyropoulou et al, 2004). The consequence of the above is the expression of a negative to ambivalent view by several teachers who believe that school cannot remove inequalities in education, not even with the use of new cognitive tools (ICT).…”
Section: Discussionsupporting
confidence: 86%
“…Funding in education, but also in the introduction of ICT, plays a dominant role in upgrading the quality of education, but also in changing pedagogical-teaching practices, according to their views. Similar findings have been found in other research, highlighting the need to support teachers through training and changing culture and practices in education (Giavrimis & Giossi, 2011), but also to increase the financial resources available to upgrade the teacher's project (Spyropoulou et al, 2004). The consequence of the above is the expression of a negative to ambivalent view by several teachers who believe that school cannot remove inequalities in education, not even with the use of new cognitive tools (ICT).…”
Section: Discussionsupporting
confidence: 86%
“…A study conducted by Chisalita and Cretu (2012) involving 120 female students in Romania revealed that they considered ICT has a high influence on the ways in which they learn and they were no longer able to prepare school activities without using type of resources. Giavrimis, Giossi and Papastamatis (2011) in their study on 162 primary teachers in Northern Greece focusing on teacher's attitude revealed that one of the main reasons for primary schools teachers' participation in ICT programmes is their interest in exploiting ICT, in both their teaching and personal lives. Yunus et al (2009) investigated students' attitude towards the use of ICT in language learning denoted that the students had positive attitudes towards ICT usage.…”
Section: Attitudes Towards the Use Of Ict Tools In Literature Lessonmentioning
confidence: 99%
“…The project design was participatory action research (McIntyre, 2008), which means the project was carried out as a co‐operative effort of the researchers and the participants of the schools (teachers, school health nurses, school catering workers, pupils and pupils' families). The tasks of the researchers were to help the participants recognise the need for development at the school level and to improve their pedagogical attitudes and knowledge related to the nutrition health project and the ICT‐based learning environment (Skinner et al , 2006; Giavrimis et al , 2011). In a project like this, learning is possible for all parties – for the school members, pupils and their families as well as the researchers.…”
Section: Introductionmentioning
confidence: 99%